THE IMPLEMENTATION OF ISLAMIC TEACHINGS IN THE POLITICAL PRACTICES OF SEYYED ALI KHAMENEI - Siswoyo Aris Munandar (Sadra International Institute, 2024)
Seyyed Ali Khamenei, the Supreme Leader of Iran, is renowned for his expertise in Qur’anic sciences and interpretation, shaping the foundation of Islamic law and teachings in Iran. This research examines Khamenei’s significant role in interpreting and applying Qur’anic teachings, detailing his educational background and deep understanding of Qur’anic exegesis. It explores how Khamenei’s Qur’anic knowledge influences his political policies and leadership style, positioning him as a pivotal figure in contemporary Iranian politics. The study analyzes Khamenei’s interpretations of the Qur’an, aiming to provide insights into his ideological influence on Iran’s socio-political landscape and policy-making. It also discusses the implications of his views on the practice of Muslim life in Iran, particularly how Qur’anic teachings are integrated into governmental policies. The research highlights Khamenei’s perspective of the Qur’an as a comprehensive guide for all aspects of life, which has not only shaped governance but also stirred controversy in terms of social, political, and individual rights. Through a critical examination of Khamenei’s thoughts and their impact, this study contributes to a deeper understanding of the dynamic interplay between religion and state in Iran.